Studi Identifikasi Faktor Faktor Pendukung Dan Penghambat Pencapaian Target Spbe Di Kota Tasikmalaya Tahun 2024 - Dewi, Putri Puspita; Tricahyono, Dodie (eProceedings of Management, 2024)
The utilization of data and correspondence innovation in government exercises is a type of e-government execution.The execution of e-government in Indonesia was developed with the issuance of Official Guideline Number 95 of 2018concerning Electronic-Based Government Frameworks (SPBE). During the 5 years that the guidelines connected withSPBE were distributed, a few deterrents were found in the execution cycle, guidelines and assets so they couldn'taccomplish the greatest objective. The point of this exploration is to show the estimation cycle of the SPBEdevelopment level record esteem in the Tasikmalaya Regional Government. The examination utilized in thisexploration alludes to PERMENPAN Number 59 of 2020. Comprises of 47 markers that will evaluate developmentlevels as indicated by current information and conditions. The screening was completed with witnesses or sourcesassociated with shrewd administration the board in the city of Tasikmalaya to find solutions to every pointer. In lightof the consequences of executing the savvy administration aspect in Tasikmalaya City utilizing the SPBE record, itshows the reception and execution of inside strategies connected with SPBE engineering, information the executives,data security, and ICT reviews. Proficient, straightforward and responsive regulatory administrations have been givento the general population through complex data innovation. The City of Tasikmalaya has prevailed with regards tobuilding a strong groundwork in the administration of unstable materials with viability, productivity, security andbetter help than the local area. Tasikmalaya City, in carrying out the savvy administration aspects, has accomplishedan excellent predicate in the SPBE file, demonstrating that the regional government has taken on a powerful shrewdadministration approach. Keywords-e-government,smart city, smart governance, SPBE, governance, Tasikmalaya.